Aspectos da ecologia de flebotomíneos (Diptera: Psychodidae) em área de ocorrência de leishmaniose visceral canina : Sinop, Mato Grosso - Thies, Sirlei Franck (2017)
The importance of leishmaniasis lies in the high incidence, wide distribution, possibility of severe forms, high mortality rates for untreated visceral leishmaniasis (LV) and high morbidity for American cutaneous leishmaniasis (ACL). Leishmania is mainly transmitted by the bite of infected female sand flies, and dog is the domestic reservoir for LV. Our aim was to study the ecoepidemiology of leishmaniasis in Sinop, Mato Grosso State. For entomological surveys, monthly collections of sand flies were carried out using CDC light traps for 12 months (05/2014 to 04/2015). Identified females were submitted to PCR (LnPCR) to detect natural infection, the positive one was sequenced. Sand flies density was correlated to climatological data and some parameters of their ecology were evaluated. For the study of hosts and reservoirs photographic cameras were used in APPs. In order to determine the canine positivity rate we used DPP and Elisa assays and to detect and characterize a Leishmania species in these dogs, PCR was used in blood and conjunctival swab specimens. A total of 62,745 sand flies were captured, mostly females (32,840), and all of them were distributed in 37 distinct species. Lutzomyia dasypodogeton was the most frequent species (87.87%), followed by L. aragaoi (4.5%). The highest frequency of sand flies, according to the ecotypes, was verified in the APPs (96.85%), as well as the highest species diversity (33 species). The highest sand flies frequency was observed in the rainy season. There was a statistically significant correlation between sand fly density and precipitation, wind speed, temperature and relative humidity. Eight species important to the epidemiology of Leishmaniasis were captured, L. antunesi was the most frequent (2.01%), collected in all months and studied ecotypes. Ecologically we obtained a Simpson’s dominance= 0.775, with Shanon’s diversity H’= 0.616, confirmed by a low equitability J’= 0.168. The greatest similarity occurred between points 19-21 located in APPs. Few species were constant in this study, with L. dasypodogeton presenting the highest abundance SISA= 1.00. Regarding the Jackknife estimaton, another 16 sand fly species could be captured in the study area. Natural infection was detected in one sample of L. antunesi, corresponding to a minimum infection rate of 0.07%, this sample was positive for Leishmania hertigi in the sequencing. In the APPs, we recorded images of several wild animals that may become reservoirs of Leishmania species, such as fox, armadillo and porcupine (Le. hertigi reservoir). The canine infection, considering at least one positive diagnostic test was, 48.96%. There were 6.94% positive samples in the DPP method, 3.13% in the Elisa assay, 28.82% in the blood PCR and 22.22% in the conjunctival swab PCR. Serological tests were less effective when compared to PCR. Blood PCR showed better performance than conjunctival swab PCR. Domestic dogs can be considered urban VL reservoirs in Sinop. The results presented in this study on sand flies and canine infection might contribute to a better targeting of preventive and control measures by the competent health agencies. Especially because Sinop is a silent municipality for VL and ACL, alerting the need for new researches in Sinop and in other municipalities presenting the same epidemiological profile, since human cases of VL may occur very soon.